1987
DOI: 10.1111/j.1600-0404.1987.tb03536.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of pyridoxine overdose neuropathy syndrome

Abstract: A newly recognised neurotoxic syndrome due to pyridoxine (B6) overdose is described. It is the largest series of B6 intoxication hitherto reported. A raised serum B6 level was present in 172 women of whom 60% had neurological symptoms, which disappeared when B6 was withdrawn and reappeared in 4 cases when B6 was restarted. The mean dose of B6 in the 103 women with neurological symptoms was 117 +/- 92 mgs, compared with 116.2 +/- 66 mgs in the control group. There was a significant difference (P less than 0.01)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
96
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(99 citation statements)
references
References 5 publications
1
96
0
2
Order By: Relevance
“…However, vitamin concentrations in blood cells tend to be a better marker of cellular stores (10 ). We describe a simple, robust, reversed-phase HPLC method with precolumn derivatization using semicarbazide (11)(12)(13) that is suitable for the simultaneous measurement of PLP, 4-pyridoxic acid (PA), and PL in plasma and red cells and application of the assay in healthy individuals, patients with chronic disease, and critically ill patients requiring intensive care.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, vitamin concentrations in blood cells tend to be a better marker of cellular stores (10 ). We describe a simple, robust, reversed-phase HPLC method with precolumn derivatization using semicarbazide (11)(12)(13) that is suitable for the simultaneous measurement of PLP, 4-pyridoxic acid (PA), and PL in plasma and red cells and application of the assay in healthy individuals, patients with chronic disease, and critically ill patients requiring intensive care.…”
mentioning
confidence: 99%
“…PLP and PL in blood were measured as their semicarbazone derivatives, pyridoxal 5Ј-phosphate semicarbazone (PLPSC) and pyridoxal semicarbazone (PLSC), respectively (12,13 ). The assay was optimized with respect to derivatization, separation, and detection.…”
mentioning
confidence: 99%
“…7 Subtle symptoms such as paresthesia and muscle weakness have also been reported in those taking doses as low as 10 mg/kg per day. 8,9 There have also been several reports of liver toxicity with prolonged highdosage use of PLP, 10, 11 but overall pyridoxine and PLP supplementation are generally well tolerated. 7,8,10,12 To our knowledge, no bleeding symptoms have been reported in those taking either pyridoxine or PLP.…”
Section: Discussionmentioning
confidence: 99%
“…A vitamin B6 toxicity has also been found to cause peripheral neuropathy [129,[131][132][133][134][135]. In 1983, Schaumburg et al [132] reported the development of PN in seven patients who were taking vitamin B6 in excess of 1g/day for several months.…”
Section: Role Of Pyridoxine In the Peripheral Nervous Systemmentioning
confidence: 99%
“…Further studies, with participants taking lower doses of vitamin B6 (90 mg-500 mg a day), also reported the development of sensory PN from vitamin B6 administration taken over one to five years. PN ceased once administration of B6 was discontinued, however, recovery took six months for most participants [133,134].…”
Section: Role Of Pyridoxine In the Peripheral Nervous Systemmentioning
confidence: 99%